IMPLIKASI PUTUSAN MAHKAHAM KONSTITUSI SEBAGAI POSITIF LEGISLATOR TERHADAP PRINSIP CHECK AND BALANCE: Mahkamah Konstitusi sebagai Positive Legislator: Implikasi Putusan terhadap Prinsip Checks and Balances di Indonesia - Sulastri, Dewi; Sanmas, Abu (LITIGASI, 2025)
The Indonesian Constitutional Court has undergone a transformation from a negative legislator to a positive legislator, particularly evident in Decision No. 90/PUU-XXI/2023, which not only annulled unconstitutional norms but also created new regulations regarding age requirements for presidential candidates. This study examines the implications of Constitutional Court decisions as a positive legislator on checks and balances, practices in the United States, Germany, and South Korea, and the reformulation of Constitutional Court authority. Employing normative legal research with statutory, conceptual, case, and comparative approaches, this study analyzes Constitutional Court decisions and practices in three countries. The findings indicate that Constitutional Court decisions acting as a positive legislator tend to shift the balance of power between the judicial, legislative, and executive branches, creating legal uncertainty and institutional conflicts. Practices in the US, Germany, and South Korea reveal that the positive legislator role requires institutional dialogue mechanisms and clear authority limitations. The implications emphasize the need for reformulating Constitutional Court authority through establishing objective criteria, strengthening checks and balances mechanisms, and developing constitutional dialogue among the Constitutional Court, Parliament, and President. This study contributes by examining comparative practices (US, Germany, South Korea) and formulating reformulation guidelines not previously developed in existing scholarship.